Comprehensive study on boil-off gas generation from LNG road tankers under simultaneous impacts of heat leakage and transportation vibration. (1st September 2020) - Wang, Xingchun; Xu, Yiling; Wang, Sujing; Xu, Qiang; Ho, Thomas C.
Abstract: The minimization and utilization of boil-off gas (BOG) during the production, storage, and transportation of liquefied natural gas (LNG) have drawn wide interests. However, current studies on quantification of BOG generation still need to be improved because the mechanical vibration impact on BOG generation has seldom been considered in most of LNG studies. In this paper, the dynamic BOG generation under both heat leakage and vibration impact during the LNG on-road transportation have been quantitatively investigated via the integration of computational fluid dynamics (CFD) and process dynamic simulations. First, a multiphase LNG model is developed to characterize the thermal energy increment due to on-road vibration effect by CFD simulations, where a user-defined function (UDF) is employed with the dynamic mesh algorithm. Next, the vibration-induced thermal energy is introduced into a process dynamic model, where a heat-leakage considered LNG tanker is simulated to quantify the total BOG generation during the LNG on-road transportation. This work for the first time addresses two root causes of BOG generation with both CFD and process dynamic simulations, which lays a solid foundation for future BOG minimization and utilization during various LNG transportation, storage, and applications.